Analisis Faktor Risiko Perdarahan Antepartum pada Ibu Hamil dengan Plasenta Previa di RSUD Y - Saputri, Nurul Aini Suria; Arbiyah, Arbiyah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Placenta previa is a major cause of antepartum hemorrhage, which can be life-threatening for both the mother and the fetus. Identifying risk factors is crucial for prevention and early management. Objective: To analyze the risk factors associated with antepartum hemorrhage in pregnant women diagnosed with placenta previa at Y Regional General Hospital. Methods: This quantitative study used a retrospective, analytical, observational study design. Medical records of pregnant women with placenta previa from 2022–2024 were statistically analyzed using the chi-square test and logistic regression. Results: Significant risk factors for antepartum hemorrhage included: age >35 years (p=0.015), multiparity (p=0.002), history of cesarean section (p=0.001), and pregnancy spacing <2 years (p=0.032). Conclusion: Advanced age, multiparity, history of cesarean section, and short pregnancy spacing significantly increase the risk of antepartum hemorrhage in placenta previa.